Archive Drift - Kroker, Arthur (Intermédialités / Intermediality, 2011)
Nothing is as purely imaginary as the digital archive. Like a brilliant specter from the vast recesses of the cultural universe, the digital archive sweeps through the night skies of the mind, turning time’s past into real-time, lighting up spatial horizons with light-space, folding the historical past into the projected future, breaking down fixed boundaries, always following the unpredictable pathways of the awaiting imagination. Never really interested in truth-telling, nor particularly loyal to the concept of bunker archeology, the digital archive is that rarest of cultural phenomenon: a code matrix tracing an uncertain arc across the human condition, projecting retrieved memories into the present, here confronting the solid matter of reality with imaginary reconstructions of the past, there gathering speed as the code matrix is propelled forward by the gravitational force-fields of the surrounding planets of society, economy, and culture, always becoming in the process something more intense, more vivid, more purely imaginary.